Muatan terubahkan oxisols dan Ultisols yang berkembang diatas batuan basalt, daerah Malili, Sulawesi Selatan=Variable charge solis of oxisols and ultisols which developed on basalt at Malili district, South Sulawesi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
ABSTRAK Mineralogical composition governed the soil charge characteristics of the three profiles. Profile I and III possessed positive 8pH, and pHo that was relatively close to the pHo of pure oxide-Fe, whilst profile II extended negative (pH and pHo < pH H2O. Hence, it was equitable to classify profile I and III as variable charge soils, and profile II as a permanent charge soil. It was predicted that the number of permanent charge in each profile was -5.01 x 10-7 x n"2, -2.33 x 10"6 x n"2 and -6.68 x 107 x n1'2 in profile I, II and III, respectively. These findings clearly indicated that profile II creates greater permanent negative charge than profile I and III, and this was due to the appearance of verrraculite. The magnitude of PZNC was profile I > profile HI > profile II, which deduced that profile I and III were more developed than profile II. The different between pH H2O and PZNC in profile II was 1.7 unit, while those in the profile I and III were 0.5 unit and 0.7 unit. Those greater value in the profile II leaded to occurrence of clay dispersion and translocation process that supports argillic horizon to exist. The different between pHo and PZNC in the profile I, II and III were 0.2 unit, 1.4 unit and 0.4 unit, respectively. The presence of permanent negative charge in the profile II caused larger different between pHo and PZNC. The larger the different between the two characters, the higher the soil permanent negative charge. Moreover, the smaller the different between the two characters, the more development soil.